EP626 Lymph vascular space invasion, an independent risk factor of sentinel node mapping failure in endometrial cancer, the sentifail study: a multicentric prospective analysis. (1st November 2019) - Sozzi, G; Re, FM; Berretta, R; Lo Balbo, G; Giallombardo, V; Capozzi, VA; Ceresi, N; Scambia, G; Chiantera, V
Abstract : Introduction/Background: Sentinel lymph node (SLN) mapping has become the gold standard for surgical staging of early stage endometrial cancer. Side-specific systematic lymphadenectomy is suggested if SLN mapping failed. The objective of this study is to identify clinical and pathological factors associated with failed mapping. Methodology: We prospectively evaluated a consecutive series of early stage endometrial cancer patients submitted to SLN mapping with indocyanine green (ICG) near-infrared compatible surgical platforms in two oncological referral centers from January 2018 to January 2019. Indocyanine green was injected intracervical. Bilateral mapping and failed bilateral SLN mapping groups were compared for clinical and pathological features. Results: Over the study period, 78 patients met the inclusion criteria. The overall, unilateral, and bilateral SLN detection rates were 88.5%, 15.4%, and 73.1%, respectively. The failed unilateral or no mapping bilateral detection rate was 26.9%. No association between patient demographic characteristics (age, body mass index, histology, grading, tumor size, myometrial invasion and FIGO stage) and SLN mapping failure was observed. Moreover, uterine manipulator or cervical grasping before ICG injection were not associated to failed mapping, while multivariate analysis identified lymph vascular space involvement (LVSI) as the only independent risk factor of SLN mapping failure [OR 4.09 (1.04–1.12), p-value: 0.04]. Conclusion: Failed SLN mapping is not a rare event andside-specific systematic lymphadenectomy is required to obtain a comprehensive surgical staging. LVSI resulted as the only independent risk factor of SLN mapping failure, probably due to the occlusion of the lymphatic capillaries and consequent failure of the tracer diffusion. Disclosure: Nothing to disclose.